1999
DOI: 10.1038/18050
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the amino-terminal domain of Cbl complexed to its binding site on ZAP-70 kinase

Abstract: Cbl is an adaptor protein that functions as a negative regulator of many signalling pathways that start from receptors at the cell surface. The evolutionarily conserved amino-terminal region of Cbl (Cbl-N) binds to phosphorylated tyrosine residues and has cell-transforming activity. Point mutations in Cbl that disrupt its recognition of phosphotyrosine also interfere with its negative regulatory function and, in the case of v-cbl, with its oncogenic potential. In T cells, Cbl-N binds to the tyrosine-phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
251
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 279 publications
(263 citation statements)
references
References 26 publications
12
251
0
Order By: Relevance
“…Indeed, Cbl is abundantly expressed in cortical neurons and contains a phospho-tyrosine recognition domain comprising an EF-hand and a SH2-like structure through which it binds phospho-tyrosine residues, followed by a hydrophobic residue at pY + 4 (fourth residue after the phospho-tyrosine). These are similar to the motifs found at phosphorylation sites Tyr185 and Tyr198 of Dab1 (Lupher et al 1997;Meng et al 1999). Previous studies showed that Cbl can ubiquitinate Dab1, at least in transfected COS7 cells (Suetsugu et al 2004).…”
Section: Down-regulating Dab1supporting
confidence: 82%
“…Indeed, Cbl is abundantly expressed in cortical neurons and contains a phospho-tyrosine recognition domain comprising an EF-hand and a SH2-like structure through which it binds phospho-tyrosine residues, followed by a hydrophobic residue at pY + 4 (fourth residue after the phospho-tyrosine). These are similar to the motifs found at phosphorylation sites Tyr185 and Tyr198 of Dab1 (Lupher et al 1997;Meng et al 1999). Previous studies showed that Cbl can ubiquitinate Dab1, at least in transfected COS7 cells (Suetsugu et al 2004).…”
Section: Down-regulating Dab1supporting
confidence: 82%
“…By cloning larger portions of STAT1 and STAT2 that included their entire SH2 domain-containing cores (Mao and Chen, 2005), we obtained soluble, monomeric material for these two proteins. In addition, we cloned, expressed, and purified the N-terminal domain of CBL (Meng et al, 1999), which contains a noncanonical SH2 domain. In total, 133 domains representing 103 proteins were used in these studies.…”
Section: Discussionmentioning
confidence: 99%
“…This alignment superimposes a four-helix bundle domain from Cbl, a ubiquitin ligase involved in cell signalling, onto the priming domain of terminal protein with a Z-score of 4.7 (PDB code 2CBL; Meng et al, 1999). Since the four-helix bundle is an abundant motif and Cbl is functionally unrelated to terminal protein, this structural similarity appears purely coincidental.…”
Section: Structure Determinationmentioning
confidence: 99%